Ubisol-QE as a Therapeutic Treatment for Paraquat Induced Neurodegeneration In Rat Model of Parkinson’s Disease - Leahy, Samantha (The Meducator, 2013)
The standard pathophysiology in neurodegenerative diseases, such as Parkinson’s disease (PD), is caused by loss of dopaminergic neurons. Mitochondrial dysfunction and oxidative stress have been implicated in these types of neuronal death. It has been shown that exposure to environmental toxins such as paraquat, a commonly used herbicide, can lead to an increase in the incidence of PD. So far, there is no effective therapeutic treatment that can halt the progression of the neurodegeneration. We have been conducting research on a water soluble formulation of CoQ10 (Ubisol-QE) and are testing its ability to protect neurons in vivo. It has previously been shown that Ubisol-QE prevents progression of neurodegeneration in rat models of PD post-injury. We wanted to determine the duration of Ubisol-QE treatment required to effectively sustain neuroprotection. Therefore, over the 8-week treatment portion of the experiment, one group of paraquat exposed rats were treated for the entire time with Ubisol-QE, while another had their treatment withdrawn after 4 weeks. We evaluated the neuroprotective effects by the number of tyrosine hydroxylase positive neurons in the substantia nigra region of the brain of animals who were given continuous treatment and those of whom who had their treatment withdrawn. The results suggest that Ubisol-QE has a significant effect after 8 weeks of treatment, indicating that longer duration of the treatment is needed. In observing the results from the neuromotor decline experiments, the treatment group had far less hind leg slips than the untreated groups, reflecting the protection that was seen in the immunohistochemical results. Consequently it can be suggested that Ubisol-QE could be an effective treatment to halt the neurodegeneration found in PD patients.